Large scale integration of renewable energy sources (RES) in the future Colombian energy system (2019)
The diversification of the energy matrix, including larger shares of Renewable Energy Sources (RES), is a significant part of the Colombian energy strategy towards a sustainable and more secure energy system. Historically, the country has relied on the intensive use of hydropower and fossil fuels as the main energy sources. Colombia has a huge renewables potential, and therefore the exploration of different pathways for their integration is required. The aim of this study was to build a model for a country with a hydro-dominated electric power system and analyse the impacts of integrated variable RES in long-term future scenarios. EnergyPLAN was the modelling tool employed for simulating the reference year and future alternatives. Initially, the reference model was validated, and successively five different scenarios were built. The results show that an increase in the shares of wind, solar and bioenergy could achieve an approximate reduction of 20% in both the CO2 emissions and the total fuel consumption of the country by 2030. Further, in the electricity sector the best-case scenario could allow an estimated 60% reduction in its emission intensity. © 2019 Elsevier Ltd